2000
DOI: 10.1248/bpb.23.1298
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Promoting Effect of an Active Component of Polyporus, Ergosterol and Related Compounds on Rat Urinary Bladder Carcinogenesis in a Short-Term Test with Concanavalin A.

Abstract: The effect of fractions from a water extract of Polyporus on bladder tumor promotion was examined using 5% sodium saccharin (SS) in a short-term test with concanavalin A (Con A) in Wistar rats. Rats were given N-butyl-N-(4-hydroxybutyl) nitrosamine (BHBN) in drinking water for one week, and then promoter alone or test samples (given orally) plus promoter was administered for 3 weeks. Treatment with the BuOH fraction isolated from the water extract showed a strong inhibitory effect against the promoter. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 1 publication
2
32
1
2
Order By: Relevance
“…Ergosterol taken up by the gut may act as a membrane antioxidant (Wiseman, 1993). Ergosterol can modify the effect of cholesterol on human cell cycle progression (Suárez et al, 2002) and has antitumor effects in cell culture (Yazawa et al, 2000) and in vivo in rats (Mitani et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Ergosterol taken up by the gut may act as a membrane antioxidant (Wiseman, 1993). Ergosterol can modify the effect of cholesterol on human cell cycle progression (Suárez et al, 2002) and has antitumor effects in cell culture (Yazawa et al, 2000) and in vivo in rats (Mitani et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the health-promoting properties of ergosterol, including the 13 antioxidant (Shao et al 2010), anti-inflammatory (Kuo et al 2011) antihyperlipidemic (Hu et al 2006), genetic expression control (Lochman and Mikes 2005) and antitumoral activities (Takaku et al 2001;Yazawa et al 2000), are closely related to the uptake doses. Furthermore, it will be important to understand how its concentration varies during the main fungi development stages.…”
mentioning
confidence: 99%
“…The occurrence of ergosterol derivatives (17.91 %) in the n-hexane extract as the predominant steroids could be due to the reported occurrence of ergosterols in yeast and fungal cell membranes functioning in same manner cholesterol does in animal cells. Research has shown ergosterol may exhibit some degree of antitumor properties [17,18]. Ergosterols are known to act as biological precursors of vitamin D2 hence can be classified as provitamins [19].…”
Section: Discussionmentioning
confidence: 99%